Revision of the cricket genus Nisitrus Saussure (Orthoptera: Gryllidae: Eneopterinae) and descriptions of five new species - Tan, Ming Kai; Wahab, Rodzay bin Haji Abdul; Japir, Razy; Chung, Authur Y.C.; Robillard, Tony (European Journal of Taxonomy, 2021)
Nisitrus Saussure, 1878 is a diurnal and monophyletic group of eneopterine crickets found in parts of Southeast Asia. Species often have vivid colourations which make them charismatic photograph subjects among macro photographers. However, their taxonomy has not been revised since their original descriptions, whereas there are also species awaiting to be discovered and described. A synoptic revision is therefore needed prior to studying the phylogenetic relationships of the genus, and before undertaking more precise studies on biogeography and evolution of traits. By holistically incorporating information about general morphology, male and female genitalia, and bioacoustics, we revise the taxonomy of these crickets and recognise 10 valid species of Nisitrus. Five new species are described: N. crucius Robillard & Tan sp. nov. from Borneo; N. danum Robillard & Tan sp. nov. from Borneo; N. hughtani Robillard & Tan sp. nov. from Sumatra; N. malaya Robillard & Tan sp. nov. from Malay Peninsula; and N. rindu Robillard & Tan sp. nov. from Borneo. We redescribe N. brunnerianus and N. insignis; describe the calls of N. malaya sp. nov., N. musicus and N. vittatus. We consider N. sumatrensis as a junior synonym of N. insignis; and N. marginata as a junior synonym of N. vittatus. Nisitrus hyalinus requires further revision. We also consider N. maculosus as a dubious name.